2008
DOI: 10.1086/527414
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration in Fast Halo CMEs and Synchronized Flare HXR Bursts

Abstract: We study two well-observed, fast halo CMEs, covering the full CME kinematics including the initiation and impulsive acceleration phase, and their associated flares. We find a close synchronization between the CME acceleration profile and the flare energy release as indicated by the RHESSI hard X-ray flux onsets, as well as peaks occur simultaneously within 5 minutes. These findings indicate a close physical connection between both phenomena and are interpreted in terms of a feedback relationship between the CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
168
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 203 publications
(196 citation statements)
references
References 44 publications
27
168
0
1
Order By: Relevance
“…Recently, based on a number of CMEs observed by the C1, C2, and C3 telescopes of Large Angle and Spectrometric Coronagraph (LASCO) for which the initial acceleration was adequately resolved, the "acceleration phase" of these CME events was empirically found to coincide with the rise phase of the associated flare X-ray emission (Zhang et al 2001). This finding has been supported by recent work of Maričič et al (2007) and Temmer et al (2008). They, however, also discovered exceptions and considerable scatter in the timing correlation.…”
Section: Introductionsupporting
confidence: 68%
“…Recently, based on a number of CMEs observed by the C1, C2, and C3 telescopes of Large Angle and Spectrometric Coronagraph (LASCO) for which the initial acceleration was adequately resolved, the "acceleration phase" of these CME events was empirically found to coincide with the rise phase of the associated flare X-ray emission (Zhang et al 2001). This finding has been supported by recent work of Maričič et al (2007) and Temmer et al (2008). They, however, also discovered exceptions and considerable scatter in the timing correlation.…”
Section: Introductionsupporting
confidence: 68%
“…However, it has been shown that the acceleration profile of CMEs tends to peak during this period, too (cf. Zhang et al, 2001;Maričić et al, 2007;Temmer et al, 2008;Berkebile-Stoiser et al, 2012). Since coronal waves are highly associated with CMEs too (Section 5.2), timing alone cannot be used to make a distinction between a flare-related and a CME-related wave launch mechanism.…”
Section: Solar Flaresmentioning
confidence: 99%
“…Though, the flare impulsive phase is often closely associated with the acceleration phase of the flare-related CMEs [173][174][175].…”
Section: Volume 35mentioning
confidence: 99%